Public private partnership in delivery of artificial insemination services - CGIAR Research Program on Livestock (2019)
This innovation was piloted by ILRI in Kenya within two donor-funded projects. While the technology is well established, the coordination of the various actors is complex; for successful implementation, each stage must be properly planned and implemented, involving dairy farmers, the veterinary directorates of county governments, and AI service providers.